2019
DOI: 10.1002/cam4.2603
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world health utility scores and toxicities to tyrosine kinase inhibitors in epidermal growth factor receptor mutated advanced non‐small cell lung cancer

Abstract: Background As the treatment landscape in patients with non‐small cell lung cancer (NSCLC) harboring mutations in the epidermal growth factor receptor (EGFRm) continues to evolve, real‐world health utility scores (HUS) become increasingly important for economic analyses. Methods In an observational cohort study, questionnaires were completed in EGFRm NSCLC outpatients, to include demographics, EQ‐5D‐based HUS and patient‐reported toxicity and symptoms. Clinical and radiologic characteristics together with outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The overall mean EQ-5D derived health utility score in this study was 0.7, which is similar to that previously reported for EGFR -TKI trial populations [ 52 , 53 ]. This suggests that patients with EGFRm + aNSCLC are generally in good health, as the score is only marginally lower than the average utility score (0.81) of the general UK population of similar age [ 54 ].…”
Section: Discussionsupporting
confidence: 88%
“…The overall mean EQ-5D derived health utility score in this study was 0.7, which is similar to that previously reported for EGFR -TKI trial populations [ 52 , 53 ]. This suggests that patients with EGFRm + aNSCLC are generally in good health, as the score is only marginally lower than the average utility score (0.81) of the general UK population of similar age [ 54 ].…”
Section: Discussionsupporting
confidence: 88%
“…In patients who experience severe (grade 3 or 4) rash, a change in therapy is also warranted. In fact, a recent trial found that third generation TKIs (such as osimertinib) had fewer skin toxicities than traditional first-generation TKIs [12]. In our patient, a change from gefitinib to osimertinib was initiated for this reason.…”
Section: Discussionmentioning
confidence: 80%
“…As well as the need to use other sources to extrapolate OS data, health-related quality of life assessment in the ADAURA trial did not readily support the creation of HSUVs for Canada. This was because the trial took place in many other countries; thus, HSUVs were assumed from real-world data from Canada [ 33 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…An age-adjustment to the utility in every state was applied [ 32 ]. Literature-based health state utility values (HSUVs) for the DF and DM health states were available from Canadian real-world evidence (RWE) [ 24 , 33 ] and are used as the reference case. Utility data in ADAURA were collected in the Short Form 36 Health Survey Questionnaire (SF-36) and needed to be mapped to the EuroQoL 5-dimensions (EQ-5D) before a Canadian tariff could be applied.…”
Section: Methodsmentioning
confidence: 99%